STUDY OF ANTIBIOTIC USAGE IN PIG FARMING IN SEBATU VILLAGE, GIANYAR REGENCY, BALI - Emia Pepa Yosa Br Ginting; Kadek Karang Agustina; Tjok Gde Oka Pemayun; Romy Muhammad Dary mufa; I Wayan Masa Tenaya; I Made Sukada; Nyoman Sadra Dharmawan (Buletin Veteriner Udayana, 2025)
The main cause of antibiotic resistance is the misuse and excess of antibiotics. Other factors are misunderstanding of antibiotic use, inappropriate antibiotic dosage, the use of broad-spectrum antibiotics and antibiotics sold freely without a doctor's prescription. The purpose of this study was to determine the percentage of antibiotic use among pig farms, the types of antibiotics used and the status of antibiotic use by pig farmers in Sebatu Village, Tegallalang District, Gianyar Regency, Bali. The study used observational and interview methods in the form of questionnaires distributed to pig farmers. Data were analyzed descriptively and then displayed in tables and figures. The percentage of respondents who used antibiotics under the supervision of a veterinarian was 56.67% (17/30 respondents) and 43.33% (13/30 respondents) of pig farmers provided independent treatment for livestock without supervision from a veterinarian. (33.33%) pig farmers obtained antibiotics from drug stores, (10%) from other farmers. The types of antibiotics used were the Tetracycline group (92.3%); Penicillin (30.7%); Sulfonamides (38.4%); Aminoglycosides (23.0%). Selecting antibiotics based on the needs of sick animals (26.67%); Selected by drug sellers (16.67%); dosage determined by drug brochures (30%); Previous experience (13.33%); Farmers' knowledge of antibiotics and their functions (63.33%); do not know (36.67%) and farmers already know that using antibiotics must be under the supervision of a veterinarian (60%); do not know (40%). The percentage of pig farmers who use antibiotics in Sebatu Village, Tegallalang District, Gianyar Regency, Bali reached 43.33% (13 farmers) independently without the supervision of a veterinarian with various types of antibiotic groups.